Vaccinia-related Kinase 1 (VRK1) Is an Upstream Nucleosomal Kinase Required for the Assembly of 53BP1 Foci in Response to Ionizing Radiation-induced DNA Damage - Sanz-García, Marta (American Society for Biochemistry and Molecular Biology, 2012)
Cellular responses to DNA damage require the formation of protein complexes in a highly organized fashion. The complete molecular components that participate in the sequential signaling response to DNA damage remain unknown. Here we demonstrate that vaccinia-related kinase 1 (VRK1) in resting cells plays an important role in the formation of ionizing radiation-induced foci that assemble on the 53BP1 scaffold protein during the DNA damage response. The kinase VRK1 is activated by DNA double strand breaks induced by ionizing radiation (IR) and specifically phosphorylates 53BP1 in serum-starved cells. VRK1 knockdown resulted in the defective formation of 53BP1 foci in response to IR both in number and size. This observed effect on 53BP1 foci is p53- and ataxia-telangiectasia mutated (ATM)-independent and can be rescued with VRK1 mutants resistant to siRNA. VRK1 knockdown also prevented the activating phosphorylation of ATM, CHK2, and DNA-dependent protein kinase in response to IR. VRK1 activation in response to DNA damage is a novel and early step in the signaling of mammalian DNA damage responses.